Abundance and Extracellular Release of Phytohormones in Aero‐terrestrial Microalgae (Trebouxiophyceae, Chlorophyta) As a Potential Chemical Signaling Source1. Issue 5 (3rd July 2020) - Pichler, Gregor; Stöggl, Wolfgang; Candotto Carniel, Fabio; Muggia, Lucia; Ametrano, Claudio Gennaro; Holzinger, Andreas; Tretiach, Mauro; Kranner, Ilse
Abstract : Phytohormones are pivotal signaling compounds in higher plants, in which they exert their roles intracellularly, but are also released for cell‐to‐cell communication. In unicellular organisms, extracellularly released phytohormones can be involved in chemical crosstalk with other organisms. However, compared to higher plants, hardly any knowledge is available on the roles of phytohormones in green algae. Here, we studied phytohormone composition and extracellular release in aero‐terrestrial Trebouxiophyceae. We investigated (a) which phytohormones are produced and if they are released extracellularly, and if extracellular phytohormone levels are (b) affected by environmental stimuli, and (c) differ between lichen‐forming and non‐lichen‐forming species. Three free‐living microalgae ( Apatococcus lobatus, Chloroidium ellipsoideum, and Myrmecia bisecta ) and three lichen‐forming microalgae ( Asterochloris glomerata, Trebouxia decolorans, and Trebouxia sp.) were studied. Algae were grown on solid media and the following cellular phytohormones were identified by ultra‐high‐performance liquid chromatography coupled with tandem mass spectrometry (UHPLC‐MS/MS): indole‐3‐acetic acid (IAA), indole‐3‐butyric acid (IBA), abscisic acid (ABA), gibberellin A4 (GA4 ), and zeatin (ZT). Furthermore, IAA, IBA, ABA, jasmonic acid (JA), gibberellin A3 (GA3 ), and GA4 were found to be released extracellularly. IAA and ABA were released by all six species, and IAA was the most concentrated. Phytohormone release was affected by light and water availability, especially IAA in A. glomerata, Trebouxia sp., and C. ellipsoideum . No clear patterns were observed between lichen‐forming and non‐lichen‐forming species. The results are envisaged to contribute valuable baseline information for further studies into the roles of phytohormones in microalgae.